Physical fitness changes in adolescents due to social distancing during the coronavirus disease pandemic in Korea - Lee, Kwang-Jin; Seon, Se-Young; Noh, Byungjoo; An, Keun-Ok (PeerJ, 2022)
Background At least 60 min of moderate-intensity physical activity per day is recommended for physical and mental health of adolescents. Schools are one of the most suitable places for promoting students’ health as it is a place where vigorous physical activity occurs. However, the physical activity of students is threatened because schools are closed worldwide owing to the coronavirus disease (COVID-19) outbreak in 2019. Therefore, this study aimed to analyze the physical fitness changes in 27,782 Korean adolescents during the pandemic and present alternative education and health policies to the school. Methods We included 29,882 middle school students (age: 13–15 years; males: 14,941, females: 12,841) in Korea from 2019 to 2021 . Participants’ physical fitness at school was measured using the physical activity promotion system (PAPS) manual developed to measure students’ physical fitness. Physical fitness variables included body mass index (BMI), 20 m shuttle run, handgrip strength, sit-and-reach, and 50 m run. Results The COVID-19 pandemic has had a negative impact on the BMI and cardiorespiratory endurance of Korean middle school students. Specifically, male students’ BMI increased, while body composition, cardiorespiratory endurance, and grip strength decreased significantly. Female students showed significant decreases in BMI and sit-and-reach test scores. It is clear that the physical fitness level of adolescents decreased by a greater degree after the COVID-19 pandemic than before, and the decrease in the physical fitness level of male students was noticeable. Therefore, a lesson strategy should be prepared that considers the contents and methods of physical education classes to improve the physical fitness level of male and female adolescents. Conclusions Fitness-based classes suitable for online methods should be urgently added as alternative physical education classes to prepare for the second COVID-19 outbreak. In addition, it is necessary to create an environment in which physical activity is a possibility in physical education classes, in any situation using artificial intelligence and virtual reality.
Keywords: Physical activity; Physical fitness level; Middle school students